Atrakcyjność inwestycyjna jako determinanta napływu bezpośrednich inwestycji zagranicznych do Polski - Kraciuk, Jakub (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Globalization processes taking place all over the world cause that investors look for a place for conducting their investment activity in various countries. As research results of different international institutes show, Poland has become an attractive country for foreign investors who place here their investments, moving them from developed countries. In the paper there was presented a place of Poland in rankings of its attractiveness for foreign investors as well as strengths and weaknesses of our country as a place attracting foreign investors. There were also pointed out the most important activities which should be taken up in order to draw more investors and foreign investments to our country. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 99-106